The Relationship Between Nutritional Status, Vegetable Consumption and Physical Activity with Age of Menarche in Adolescent Girls - Rachelya Nurfirdausi Islamah; Dwiana Ocviyanti (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background:Menarche is the first menstrual period and marks the maturity of an adolescent girl's body. In the last decade, there has been an increase in nutritional status of children and adolescents which is often associated with an accelerated age of menarche. Several studies have shown a strong relationship between physical activity, body mass index (BMI) with the age at which menarche occurs in teenage girls. The habit of consuming certain foods such as meat and fast food is proven to accelerate the age of menarche due to an increase in fat levels. This study aims to evaluate the relationship between age of menarche with BMI, physical activity, and vegetable consumption. Methods: This research was conducted using cross-sectional study design. Participants had been filtered by inclusion criteria and exclusion criteria. Selected participants then had their height and weight measured, and filled out an online questionnaire regarding menarche and physical activity. Participants also underwent a 24-hour recall interview to determine their vegetable consumption. Results: Fifty-two participants were recruited in this study. Most of them were 12 and 13 years of age (42.3% each). Based on the results of Kruskal-Wallis test, there was no relationship between age of menarche and BMI (p = 0.071), between age of menarche and physical activity (p=0.251) and between age of menarche and vegetable consumption (p=0.753) Conclusion: In conclusion, based on the results of this study, we did not find any correlation between the age of menarche and BMI, physical activity and vegetable consumption among adolescent girls in West Java region.